Detergent-free mass spectrometry of membrane protein complexes. - Hopper, J; Yu, Y; Li, D; Raymond, A; Bostock, M; Liko, I; Mikhailov, V; Laganowsky, A; Benesch, J; Caffrey, M; Nietlispach, D; Robinson, C (2013)
We developed a method that allows release of intact membrane protein complexes from amphipols, bicelles and nanodiscs in the gas phase for observation by mass spectrometry (MS). Current methods involve release of membrane protein complexes from detergent micelles, which reveals subunit composition and lipid binding. We demonstrated that oligomeric complexes or proteins requiring defined lipid environments are stabilized to a greater extent in the absence of detergent.